Post-operative Lumbar Discitis: A series of 108 cases; Management & Outcome Experience (Bangladesh Journal of Neurosurgery, 2026)
Objective: Post-operative lumbar discitis continues to be a challenge in terms of diagnosis and variability of management. The aim of the study was to retrospectively evaluate the outcome of management of postoperative discitis (POD). Materials and Methods: A total of 108 patients treated for POD were included in the study. Clinical, radiological, and laboratory data of all patients were collected and evaluated. All patients were treated initially with bed rest, antibiotic therapy after radiological diagnosis and later surgical management was advised. Surgical management undertaken for most of the patients except 21 patients had conservative management, who denied to operative management. Discitis exhibits a bimodal age distribution, with peaks in early childhood and after age of 50. A male predominance is seen. Risk factors for discitis include diabetes, old age, immunosuppression, IV drug use, alcoholism, and renal failure. Although rare, there is an increased risk of discitis following invasive spinal procedures, estimated at 0.5% for anterior cervical discectomy and 0.25% for lumbar discectomy, with an overall rate of 0.1 to 4% of all invasive spinal procedures. Postoperative discitis accounts for approximately 20-30% of cases of discitis.2All cases were followed clinically with laboratory and radiological investigations. Results: Surgical management gives early relieve of symptoms than conservative. Conclusion: Early diagnosis and proper management are the keys to successful outcome of postoperative spndylodiscitis. Surgical debridement and fusion are aggressive, but fruitful and early recovery for discitis management.Bang. J Neurosurgery 2024; 14(1): 35-37